The prevalence and co-occurrence of hematological complications at the time of diagnosis of chronic hepatitis C in Poland: a cross-sectional study. Issue 9 (September 2016) - Pierucka, Magdalena; Stalke, Piotr; Zagożdżon, Paweł; Smiatacz, Tomasz; Zaucha, Jan M.
Abstract : Objectives: To evaluate the frequency, co-occurrence, and risk factors for hematological complications at the time of diagnosis of chronic hepatitis C (CHC). Methods: This study included 1237 patients with CHC aged 18–88 years diagnosed in the years 1998–2010 in the Pomeranian region of Poland. Clinical data, cell blood count, liver biopsy, and biochemistry results were obtained retrospectively. Results: Hematological complications were found in 31% of patients. The most frequent complication was thrombocytopenia (23.8%). The multivariate analysis showed a 5.1-fold increased risk ( P <0.05) of at least one additional hematological complication in patients with thrombocytopenia. The greatest increase in risk (7.3) was related to leukopenia and cryoglobulinemia (2.3). The risk of leukopenia was correlated with the severity of thrombocytopenia. The risk of leukopenia and thrombocytopenia increased significantly from, respectively, stages 3 and 2 of liver fibrosis compared with patients without fibrosis. Conclusion: In patients with CHC, decreases in cell blood count occur quite frequently. The most often is mild and solitary thrombocytopenia, but if severe, it may be accompanied by leukopenia, especially in women. The presence of thrombocytopenia and leukopenia in patients with CHC may indicate advanced liver fibrosis or its final stage: cirrhosis. Abstract : Supplemental Digital Content is available in the text.